Stability And Thermal Conductivity Of Graphene And Barium Titanate (Iv) Nanofluid With Different Volume Concentrations - Zulkifli, Noor Nazirulsyahmi (Universiti Sains Malaysia, 2021)
The emerging of nanofluid as great potential coolant to be implemented in various of applications due to its superior thermal properties has attracted many researchers to studies this technology. This experiment aims to evaluate the stability and thermophysical characteristic of the graphene and barium titanate (IV) nanoparticle in distilled water as nanofluid for electronic cooling application. Synthesis of both nanofluid was done through two-step method, where the mixture of nanoparticles will be stirred using magnetic stirrer for 15 minutes, followed by probe sonication for 40 minutes under 0.5 cycle and 50% amplitude. Based on visual observation, since after 1 day from the sonication process, graphene nanofluid shows sedimentation while barium titanate (IV) shows no sedimentation until 7 days where the height of white layer reduced for barium titanate (IV) with 0.3% vol concentration gradually occurs. Graphene and barium titanate (IV) nanofluid with 0.3% vol concentration shows the highest thermal conductivity enhancement of 34.9% and 39.16% respectively. While graphene with surfactant for both % vol concentration shows the same trend of thermal conductivity enhancement with the range of 1.49% up to 30.57%. The addition of surfactant assists in term of particle suspension in the fluid however SDBS surfactant is not suitable with barium titanate (IV) due to the diverse affect in thermal conductivity. The thermal conductivity increased as the nanoparticle concentration increases.